Bullous lichen planus. - Milano, A. (European Journal of Pediatric Dermatology, 2013)
A 9-year-old girl came to our observation. Her family history highlighted rheumatoid arthritis in a maternal aunt; her recent medical history put in evidence the appearance in the summer of about 1 cm in diameter red-purple roundish lesions on the thighs. At the end of August, new itchy lesions involved the four limbs, the trunk and lips; she received a diagnosis of pityriasis lichenoides and was treated with antibiotics and antiviral drugs without result. The day before our visit the girl underwent two biopsies of a papular lesion from the right arm and of a bullous lesion from the left leg. The physical examination showed on the feet bullous, 2 cm in diameter lesions on erythematous-violet skin (Fig. 1) and erythematous, conflent, 2 cm in diameter, purple papules on her wrists (Fig. 7), on the back of the hands (Fig. 6) and the upper part of the trunk (Fig. 5), where there were also papules in linear distribution (Koebner’s sign) and scaling lesions with rhagadiform erosions on the lips (Fig. 7). Dermoscopy examination (Fig. 8) showed roundish pearly-white, branched structures; at their periphery there were pigmented, red or brownish punctate or sometimes radial structures. These findings led to the diagnosis of bullous lichen planus. Indirect immunofluorescence did not put in evidence antibodies directed against the epidermis or against the dermo-epidermal basal membrane, excluding the diagnosis of lichen pemphigoides. We prescribed topical therapy, corticosteroid on non bullous lesions, corticosteroid and antibiotic on the bullous lesions. After 10 days we visited again the patient; the bullous lesions of the feet had regressed (Fig. 2), the itching had improved. The histological examination of the papular lesion showed hypergranulosis, degeneration of the basal layer, lymphocytic band infiltrate in the superficial dermis (Fig. 3 and inset) and that one of the bullous lesion dermo-epidermal cleavage (Fig. 4), confirming the diagnosis of bullous lichen.